A crítica de Hannah Arendt aos direitos humanos: uma reconstrução sobre o amor mundi - Campos, João Pedro Andrade de (2019)
Understood as the result of a historical process or political assertions and claims, the fact is that Human Rights have been a major theme since the enactment of the Declaration of Independence of the United States of America in 1776 and the Declaration of the Rights of Man and of the Citizen in 1789 fruits, respectively, of the American and French Revolutions, these two revolutions being also the backbone of the search and the realization of Rights that stretches and is based on a Constitutional spirit. However, while we may and should look to these and other similar documents, in order to seek enlightenment for real issues of our time, we recurrently face issues that overlap with theory and challenge our political practice. By this way, in this dissertation, we have as motto to discuss, from the figures of the stateless people and the refugees, what is the place of these people in the middle of an evident inefficacy of legal protection of which they suffer given their condition of loss of national bond, which mobilizes in the political thinking of Hannah Arendt a parallel reflection to what she means by Responsibility and Love to the World. We will therefore think, on the one hand, of the insufficiency of the alleged universalization of rights based on Arendt's critiques of this model and, on the other hand, revisit in the author's thinking elements that contribute to this debate under a bias that favors constitution of the public sphere. To do so, we will first resort to the sense of Political Freedom that has permeated both the events of the American Revolution and those of the French Revolution, seeking to understand how this concept influences, from the constitution of a Political Body to the very articulation of a fecund public space by free agents. In this sense, we will also seek to highlight, based on these reflections, that in Arendt's political thought there is a link between civic and political participation in public space with the wide effectiveness of Rights, which can refer to a peculiar conception of Republicanism, for emphasizing the community commitment rooted in the fulfillment of rights and duties.